Study about Quality of Education and Factors affecting Quality Education in Indian Context - Kaur, Sonpreet; Batra, Roopali (Universal Research Reports, 2018)
The precise meaning of education quality and the path to improvement of quality are often left unexplained. Examined within context, education quality apparently may refer to inputs (numbers of teachers, amount of teacher training, number of textbooks), processes (amount of direct instructional time, extent of active learning), outputs (test scores, graduation rates), and outcomes (performance in subsequent employment). Additionally, quality education may imply simply the attaining of specified targets and objectives. More comprehensive views are also found, and interpretation of quality may be based on an institution’s or program's reputation, the extent to which schooling has influenced change in student knowledge, attitudes, values, and behavior, or a complete theory or ideology of acquisition and application of learning .